2014
DOI: 10.1159/000356218
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Optimal Morphologic Response to First-Line Chemotherapy in Patients with Colorectal Liver Metastases

Abstract: Background: It has been reported that morphologic response to preoperative chemotherapy is an independent prognostic factor in patients who undergo hepatic resection of colorectal liver metastases (CLM). The aim of this study was to evaluate the predictive value of morphologic response to first-line chemotherapy in patients with CLM. Methods: We assessed 41 patients with CLM who received fluorouracil-based chemotherapy with or without bevacizumab as the first-line chemotherapy between April 2006 and June 2012.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 16 publications
2
25
1
Order By: Relevance
“…Assessing the response to preoperative treatment (chemotherapy with or without targeted agents) can be judged on tumour size [31,32], morphologic changes unrelated to size [33][34][35] and metabolic activity [36,37]. Change in size is a key indicator of response, but limitations encountered with the Response Evaluation Criteria In Solid Tumors (RECIST) have led investigators to explore alternative measures of the impact of chemotherapy on tumour size [38,39] and to define new parameters such as early tumour shrinkage and depth of response [40,41].…”
Section: Role Of Imaging In Evaluating Response To Preoperative Treatmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing the response to preoperative treatment (chemotherapy with or without targeted agents) can be judged on tumour size [31,32], morphologic changes unrelated to size [33][34][35] and metabolic activity [36,37]. Change in size is a key indicator of response, but limitations encountered with the Response Evaluation Criteria In Solid Tumors (RECIST) have led investigators to explore alternative measures of the impact of chemotherapy on tumour size [38,39] and to define new parameters such as early tumour shrinkage and depth of response [40,41].…”
Section: Role Of Imaging In Evaluating Response To Preoperative Treatmentioning
confidence: 99%
“…Change in size is a key indicator of response, but limitations encountered with the Response Evaluation Criteria In Solid Tumors (RECIST) have led investigators to explore alternative measures of the impact of chemotherapy on tumour size [38,39] and to define new parameters such as early tumour shrinkage and depth of response [40,41]. It has been shown that when treatment includes biological agents, such as bevacizumab, size is a poor predictor of outcome compared with non-size-based morphological criteria [35,34]. PET-CT is increasingly used to measure response in oncology, but its role when added to cross-sectional imaging to assess response in CRC metastases needs to be further explored [36,37].…”
Section: Role Of Imaging In Evaluating Response To Preoperative Treatmentioning
confidence: 99%
“…This new evaluation system will provide a good prognostic factor for the response of patients with liver metastasis to therapy. These results were published in Digestion in 2014 [13]. Ohshima et al [unpubl.…”
Section: Summary Of the 9th Annual Meetingmentioning
confidence: 84%
“…UGT1A1 polymorphism was a prognostic factor for leukocytopenia due to the FOLFIRI-based regimen. Yoshita et al [13] presented a new system for evaluation of the optimal morphologic response of colorectal cancer patients with liver metastasis to chemotherapy. RECIST is a standard system for the evaluation of solid tumors worldwide.…”
Section: Summary Of the 9th Annual Meetingmentioning
confidence: 99%
See 1 more Smart Citation